Reconstructing Islamic Religious Education in the Era of Artificial Intelligence (AI): an Opportunity for Revival - Rozaanah Rozaanah (ASSUNNAH PRESS, 2024)
This article discusses the impact of the implementation of artificial intelligence technology (AI) in Islamic religious education, in particular about the understanding and practice of Muslim religion as well as critical aspects that need to be considered. This article aims to investigate how AI technology affects the paradigm and methods of Islamic education, as well as its impact on the understanding and practice of Muslim religion. Moreover, this article aims to identify critical aspects that need to be considered in order not to sacrifice traditional and ethical values in the formation of the character of religious future generations. A case study analysis and research related to the use of AI technology in Islamic religious education is used to identify its impact on student understanding, changing learning paradigms, as well as challenges and opportunities faced. Data from various studies show that AI technology has improved accessibility, personalized learning experiences, and adaptive instruction within Islamic religious education. However, there are also changes in the understanding and practice of religion, as well as the challenge of preserving traditional and ethical values. The implementation of AI technology has changed the paradigms and methods in Islamic religious education. Therefore, a balanced approach is needed between AI technology and traditional approaches to ensure that important aspects such as reflection, contemplation, and discussion remain preserved in the formation of religious character.